Outcome of TACE treatment in HIV infected patients with hepatocellular carcinoma - Kong, Lingxiang (Sci Rep, 2021)
The surgical treatment and transcatheter arterial chemoembolization (TACE) rate of human immunodeficiency virus (HIV)-infected hepatocellular carcinoma (HCC) patients is relatively low in West China. For various reasons, most patients do not receive timely surgical treatment. Upon transfer to an infectious disease centralized hospital, they were already classified in the Barcelona Clinic Liver Cancer (BCLC)-B stage. A total of 2249 BCLC-B HCC patients were analyzed. The eligible population was divided into three groups for analysis of survival and prognostic factors; These were 21 HIV infected (HIV+) HCC patients treated with TACE (TACE+), 1293 non-HIV-infected (HIV−) HCC patients treated with TACE, and 150 HIV− HCC patients who only receive medication (TACE−) as a second control group. After 1:2 matching, 1- and 2-year survival of HIV+ TACE+ and HIV− TACE+ groups was 64.3% and 76.5% (P = 0.453) and 45.5% vs. 50.0% (P = 0.790) respectively. We also compared one and two-year survival between HIV+ TACE+ and HIV− TACE−. One-year overall survival was 64.3% vs. 45.7% (P = 0.097) and 2-year survival was 45.5% vs. 7.1% (P = 0.004). Multivariate analysis showed that the most important prognostic factors for survival were serum alpha-fetoprotein (AFP) and Child–Pugh score and tumor size, while HIV status had no significant effect on prognosis statistically. CD4 levels below 200 may increase the risk of opportunistic infection after surgery, but after anti-infection and systematic supportive therapy, it has no effect on survival. HIV+ patients should have the same treatment opportunities as HIV− patients. If the patient's immune status permits, we suggest that early TACE treatment should be administered to BCLC-B HCC patients, regardless of HIV infection.